Roam/MNL a visual solution to the notoriety of the Quiapo Market District - Guerrero, Janina A.
Every day, hundreds of people go to Quiapo, and make it out unharmed with all their possessions intact. They, I guess, are the smarter ones who are too good to be outsmarted by the professional thieves of the Quiapo Market District. Quiapo is notorious.There is no denying that it is also dangerous, crowded, and--for the lack of a more accurate word-- mucky. However, you can also see it as a placed filled with adventure--one that is alive and vibrant. It's a matter of perspectives. How do you get people to see that?--to see past its notoriety? By letting them have a better Quiapo experience. Tailor it. Show that with proper preparation and a bit common sense, you're less likely to be a victim of its predators. So the real question is: how do you prepare people to go to Quiapo? Show them what to expect, understand how they learn places, and let them know that despite Quiapo's shady reputation, there's always a way not to fall into harm's way. This study will show you the process of getting there. This study shoes how exactly I got to say that: by looking into how people learn, how people learn places, how people saw Quiapo, and how exactly to prepare for it.